Current Trends and Results of Endovascular Treatment of Unruptured Intracranial Aneurysms at a Single Institution in the Flow-Diverter Era - Petr, O.; Brinjikji, W.; Cloft, H.; Kallmes, D.F.; Lanzino, G. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: During the past several years, the number of unruptured aneurysms treated with endovascular techniques has increased. Traditionally, coil embolization was the treatment of choice for these lesions; however, recently flow diversion has become a viable, and in some cases superior, treatment option. The current single-center study presents results and trends of endovascular treatment with flow diversion and coil embolization in an unselected group of patients with unruptured intracranial aneurysms in a “real world“ setting during the flow-diverter era.MATERIALS AND METHODS: Three hundred ten patients with 318 treated unruptured aneurysms from June 2009 to May 2015 were included. Patient demographics, clinical characteristics, aneurysm/treatment characteristics, and outcomes were collected prospectively. We studied the following: intensive care unit admission/reasons, perioperative and mid-/long-term complications, target aneurysm rupture, retreatment/recurrence rates, and long-term neurologic outcome using the mRS.RESULTS: The flow-diverter group had a larger mean aneurysm size (12.3 ± 8.6 mm versus 8.7 ± 6.3 mm, P < .0001). There were no significant differences in the immediate (P = .43) and mid-/long-term complication rates (P = .54) between groups. Periprocedural neurologic morbidity and mortality rates were 2.1% and 0.5% in the coiling group and 2.5% and 1.6% in the flow-diverter group. Patients with coiling were more likely to be retreated than those with flow diversion (14.8% versus 5.7%, P = .009). Worsening of the mRS due to the target aneurysm was noted in only 3.2% of patients.CONCLUSIONS: The endovascular treatment of unruptured aneurysms can be performed with very low rates of neurologic complications. Both flow-diverter and coil therapy were safe and effective.FDflow diverterICUintensive care unitPEDPipeline Embolization Device